Analisis Sumber Pembentukan Qawa’id Al-Ahkam Beserta Sejarah Perkembangannya - Nasrulloh, Adang Muhamad (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This article is motivated by the existence of qawa'id al-ahkam as part of the method used in determining and determining a law from contemporary problems in the field of fiqh worship, as well as muamalah. The study focuses on the sources taken by the scholars in determining the rules, as well as the history of its development. knowing this, a Muslim thinker can observe and understand the process of forming these rules. Literature study with descriptive analysis approach as a research method. Primary and secondary sources are obtained from books, journals, and papers. The results showed that Qawa'id al-ahkam is a product of ijtihad sourced from the Qur'an, hadith and ijma' shabat, and is a generalization of fiqh themes spread among the imams of the madhhab, starting from the source then giving birth to rules then giving birth to branch rules on each main rule. The history of development starts from the period of the Prophet Muhammad, companions, tabi'in and tabi'ut tabi'in, development and opening, and progress.